A description logic based approach to formalizing the information bearing capability of paths in ER schemata. Issue 3 (10th August 2015) - Xu, Kaibo; Feng, Junkang; Crowe, Malcolm; Liu, Lin
Abstract : Purpose: – The purpose of this paper is to show how description logics (DLs) can be applied to formalizing the information bearing capability (IBC) of paths in entity-relationship (ER) schemata. Design/methodology/approach: – The approach follows and extends the idea presented in Xu and Feng (2004), which applies DLs to classifying paths in an ER schema. To verify whether the information content of a data construct (e.g. a path) covers a semantic relation (which formulates a piece of information requirement), the principle of IBC under the source-bearer-receiver framework is presented. It is observed that the IBC principle can be formalized by constructing DL expressions and examining constructors (e.g. quantifiers). Findings: – Description logic can be used as a tool to describe the meanings represented by paths in an ER schema and formalize their IBC. The criteria for identifying data construct distinguishability are also discovered by examining quantifiers in DL expressions of paths of an ER schema. Originality/value: – This paper focuses on classifying paths in data schemas and verifying their formalized IBC by using DLs and the IBC principle. It is a new point of view for evaluation of data representation, which looks at the information borne by data but not data dependencies.